Harry Pirie-Gordon and the Palestine Guide Books. (November 2012) - Gill, David W. J.
Abstract : Harry Pirie-Gordon (1883–1969) was responsible for the preparation of a series of guidebooks published by the Palestine News immediately after the First World War. The information had been prepared for the British attack on Palestine. Pirie-Gordon first went to Syria in 1908 ostensibly to study Crusader castles. He took part in the survey of the Syrian coast around Alexandretta and worked as a foreign correspondent for The Times. Pirie-Gordon was commissioned in the Royal Navy Volunteer Reserve (RNVR) and initially worked through the Arab Bureau in Cairo. After a spell in Salonica, he was commissioned in the Army, returned to Cairo, and took responsibility for the publication of the Palestine News for the Egyptian Expeditionary Force. Allenby's campaign in Palestine drew on the developing technology of aerial photography to prepare accurate maps of troop dispositions.